Antecedent of Organizational Citizenship Behavior Variables: Gender as Moderator - Ni Luh Putu Sariani; I Gede Aryana Mahayasa; A.A. Istri Agung Maheswari; I Made Purba Astakoni; Ni Made Satya Utami (Syntax Corporation Indonesia, 2022)
is study was conducted to examine the influence of workplace spirituality on job satisfaction; workplace spirituality on organizational citizenship behavior (OCB); workplace spirituality on organizational commitment; job satisfaction on organizational citizenship behavior; organizational commitment on organizational citizenship behavior; and gender role as a moderating variable on the influence of job satisfaction, workplace spirituality, organizational commitment on OCB. The survey was performed in all public notary offices in Bangli Regency, with 76 permanent staff serving as respondents. The Partial Least Square (SEM PLS) strategy was utilized to analyze the data. Before the model is pronounced excellent, the results of the entire model assessment are based on the value of Q-Square Predictive Relevance (Q2), R-Square (R2) and Goodness of Fit (GoF). The test findings show that workplace spirituality (WPS) has a substantial beneficial impact on job satisfaction, indicating that the hypothesis is correct. The hypothesis is accepted because the test findings show that workplace spirituality (WPS) positively influences organizational citizenship behavior. The test findings show that workplace spirituality (WPS) has a substantial favorable influence on organizational commitment, indicating that the hypothesis is correct. The hypothesis is rejected because the test findings show that job satisfaction (JS) has no influence on OCB. The hypothesis is accepted because the test findings show that employee organizational commitment has a strong beneficial influence on organizational citizenship behavior. As a consequence of the hypothesis testing on gender as a moderator, it can be concluded that gender is not a moderator in the accepted model.